Peningkatan Peran Relawan Pajak Dalam Upaya Asistensi Pelaporan SPT Tahunan Di KPP Pratama Blora - Warno; Mufidah, Siti Kharirotul; Agustina, Mega; Ashari, Anggita Rachma; Noviana, Eva; Rosida, Nisa Fatma; Zahra, Rafika Az; Cahyani, Sinta Nur; Masyruroh, Kholifatun (The Community Engagement Journal, 2023)
According to Article 1 number 9 PER-12/PJ/2021, tax volunteers are individuals who voluntarily allocate their time, energy, knowledge, and expertise to actively participate in tax education activities. The program aims to provide tax education and assistance through collaboration with partner organizations or tax centers, involving both students and non-students. These volunteers engage in community service by offering services, education, and raising awareness about taxation to taxpayers visiting KPP Pratama Blora and the general public. They utilize modern information technology, specifically in the E-filing and e-SPT menus, to assist individual taxpayers who earn income from employers or independent work. The primary goal is to educate taxpayers so that they can file their Annual SPT conveniently from home in the subsequent year, eliminating the need to visit KPP Pratama Blora. Keywords: Education, Tax, Service, Volunteers